Geopolitics of Russia's Heartland and its Relation to Ruskiy Mir Ideology - Firmansyah, Adrian Maulana; Rezasyah, Teuku; Wibawa , Satria (Jurnal Locus Penelitian dan Pengabdian, 2025)
In this research, which will discuss the strategy and objectives of the Heartland geopolitical concept carried out by Russia and its relationship with the Ruskiy Mir ideology as the main goal of politics and culture in expanding its power and influence over the countries of the former Soviet Union. Using the theoretical approach of offensive realism and classical geopolitical theory, this research discusses how the concept of Heartland and Ruskiy Mir as the main goal in Russian foreign policy, especially in the Ukrainian conflict. Where in this study tells that the goal of Russian foreign policy is very ideological, where Russia has the legitimacy of the former Soviet region in achieving the goal of Ruskiy Mir.